ASUPAN ENERGI, PROTEIN, DAN STATUS GIZI DENGAN KADAR UREUM PADA PENDERITA PENYAKIT GINJAL KRONIK DENGAN HEMODIALISA - Wahyuni, Sri Era (Politeknik Kesehatan Kemenkes Bengkulu, 2014)
Energy and protein intake decreased menurun (<1600 kkal and <40 gr) in patients with CKD RSUD M.Yunus Bengkulu, which can affect the nutritional status of the state can be seen from the LLA.The purpose of this study to examine the relationship of energy intake, protein and nutritional status based on LLA with urea levels in patients with CKD undergoing hemodialysis in hemodialysis installation RSUD dr. M. Yunus Bengkulu in 2013. Type a descriptive analytic study using cross-sectional research design with the independent variables (intake of energy, protein, nutritional status) and the dependent variable (urea levels). Total population of 140 people with 58 sample was taken by purposive sampling technique. The results of this study found that there was no significant correlation between energy intake with urea levels, there was a significant association between the intake of protein with urea levels and no significant correlation between the levels of nutritional status on penderta urem CKD undergoing hemodialysis in hemodialysis Installation RSUD dr . M. Yunus Bengkulu in 2013.